Estimation of the influence of ovulation induction от the state of breast in women in extracorporal fertilization program from results of MW mammography - F. K. Alibakhshova; S. M. Ipen; T. V. Lopatina; N. I. Rozhkova (Бюллетень сибирской медицины)
The results of check-up of 65 women with sterility in extracorporal fertilization (EF) program are presented. Radiothermometry was used to estimate the influence of ovulation induction on the state of breast. The dependence of changes of breast temperature on the patients’ age, pregnance in EF program, scheme of ovulation induction, number of EF attempts, gonadotrophin dose, amount of oocytes received in the EF program, presence of Ovarian HyperStimulation Syndrome (OHSS) , and level of preovulatory E2 have been analyzed. A tendency to an increase of breast temperature in women in the Assisted Reproductive Treatment (ART) program has been revealed. It correlates with the number of EF attempts, gonadotrophin dose, amount of received oocytes, presence of OHSS, and level of preovulatory estradiol, which may be indicative of increased proliferative activity in this cohort of patients. The method of microwave radiothermometry can be used to estimate and monitor the functional state of breast in women of any age without dose load.